Analisis Pengelolaan Limbah Konstruksi pada Proyek Pembangunan Gudang Pabrik PT Amtra New Factory di Tigaraksa, Tangerang - Tira Rahmaniar; Mahmud Budiono; Nurvita Anggraeni; Depiq Ruslan Taufiq; Deni Bachtiar (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This research aims to analyze solid waste management in the warehouse Factory Construction Project in Tigaraksa, Tangerang. The research method used field observation, interviews, dan descriptive analysis of construction waste management practice. The result show that the main source of waste comes from pile foundation work with the largest composition being excavated soil (55%), Waste management has implemented the 3R principles (Reduce, Reuse, Recycle) in according with law number 18 of 2008 concerning Waste Management, althouht improvement are still needed in documentation aspects and temporary storage facilities, and worker training to optimize sustainable construction waste management.